Description of Acinetobacter kanungonis sp. nov., based on phylogenomic analysis. Issue 6 (15th June 2021) - Das, Lipika; Deb, Sushanta; Das, Subrata K.
Abstract : A novel strain of a member of the genus Acinetobacter, strain PS-1 T, was isolated from the skin of fresh water pufferfish ( Tetraodon cutcutia ) collected from Mahanadi River, India. Cells were Gram-stain-negative, aerobic, coccoid and non-motile. The predominant polar lipids were diphosphatidylglycerol (DPG), phosphatidylglycerol (PG), phosphatidylethanolamine (PE) and phospholipid (PL) and the cell wall sugars were glucose, galactose and ribose. The major cellular fatty acids of PS-1 T were C18 : 1 ω9 c (30.67 %), C16 : 1 ω7 c (19.54 %), C16 : 0 (15.87 %), C12 : 0 (7.35 %) and C12 : 0 3-OH (6.77 %). The genome size was 3.5 Mbp and the DNA G+C content was 41.97 %. Gene ontology study revealed that the major fraction of genes were associated with biological processes (53.99 %) followed by molecular function (30.42 %) and cellular components (15.58 %). Comparisons of 16S rRNA gene sequences revealed 97.94–97.05 % sequence similarity with the closely related type strains of species of the genus Acinetobacter . The average nucleotide identity (ANI) and average amino acid identity (AAI) of PS-1 T with reference strains of species of the genus Acinetobacter with validly published names were bellow 95–96 and the corresponding in-silico DNA–DNA hybridization (DDH) values were below 70 %. A phylogenomic tree based on core genome analysis supported these results. Genotypic and phenotypic characteristics of PS-1 T indicate that the strain represents a novel species of the genus Acinetobacter and the name Acinetobacter kanungonis sp. nov. is proposed. The type strain is PS-1 T (=JCM 34131 T =NCIMB 15260 T )